Resenha do livro Intelligence Sharing, Transnational Organized Crime and Multinational Peacekeeping - Nobre, Fábio Rodrigo Ferreira (Revista Brasileira de Estudos de Defesa, 2022)
Resenha de: Chido, Diane E., 2018. Intelligence Sharing, Transnational Organized Crime and Multinational Peacekeeping. Palgrave MacMillan. 110p. ISBN: 9783319711829. https://doi.org/10.1007/978-3-319-71183-6